The concept of «Cult» in the linguistic picture of the world - Rysbayeva Г.Қ.; Issayeva Ж.Т.; Tungushbayeva Ғ.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
Whatever the concept of «Cult» is one of the original concepts in the spiritual and cultural conceptual systems of the people. Spiritual culture is known through the views of manaccording to on the environment, religious views, beliefs, character, abilities and notion of the cult is very complex. The study of cultic vocabulary is not a study of religion, but an understanding, a comprehensive consideration of the early spiritual heritage of the people, spiritual and cultural life, natural scientific life, beliefs, customs, traditions through a language. Every nation has its own image of the world, because language is not only thinking, means of relations, but also a spiritual and cultural mirror of the whole ethnos. In the system of the concept of «Cult», the cognitive-linguistic models of the words «syiynu», «jalbarynu», «tabynu», «kurmeteu» have special importance. Through the concept it is possible to define a national outlook, thinking, knowledge of the people.